PROBLEM EDUCATIONAL ACTIVITY OF MILITARY EDUCATION TEACHERS BEFORE THE FUTURE CONSTITUTION AS AN INCREASE (American Journal of Interdisciplinary Research and Development, 2023)
The article discusses the nature, content, basic concepts and categories of problem-based teaching and its role in increasing the knowledge activity of students in the system of higher professional education.